Immediate Effects of Ankle Dorsiflexor Facilitation Dynamic Taping on Static and Dynamic Balance and Gait Speed in Stroke Patients With Foot Drop - Jin-gu Im; Suhn-yeop Kim (Korean Research Society of Physical Therapy, 2022)
Background: Foot drop is a common symptom in stroke patients. Tape applications are widely used to manage foot drop symptoms. Previous studies have evaluated the effects of static and dynamic balance and gait on foot drop using kinesiology tape; however, only few studies have used dynamic tape application in stroke patients with foot drop. Objects: The purpose of this study was to investigate the immediate effects of dynamic taping, which facilitates the dorsiflexor muscle, on static and dynamic balance and gait speed in stroke patients with foot drop. Methods: The study included 34 voluntary patients (17 men, 17 women) with stroke. The patients were randomly assigned to the experimental group (n = 17), wherein dynamic taping was used to facilitate the dorsiflexor muscle, or the control group (n = 17), wherein kinesiology taping was used. Before the taping application, velocity average, path-length average, Berg balance scale, and timed up and go test (TUG) were recorded to measure static and dynamic balance, whereas the 10-meter walk test (10MWT) was used to measure gait speed. After the taping application, these parameters were re-evaluated in both groups. Repeated measure analysis of variance was used. Statistical significance levels were set to α = 0.05. Results: Except for the 10MWT scores in the control group, significant differences were noted in all the parameters measured for static and dynamic balance and gait speed between the pre and post-test (p < 0.05). However, the parameters showed significant interaction effects between group and time in the TUG and 10MWT (p < 0.01). Conclusion: These results indicate that compared with kinesiology taping, dynamic taping used in chronic stroke patients with foot drop had a more significant effect on dynamic balance and gait speed.